Fifteen novel universal primer pairs for sequencing whole chloroplast genomes and a primer pair for nuclear ribosomal DNAs. Issue 3 (13th April 2016) - Zhang, Ting; Zeng, Chun‐Xia; Yang, Jun‐Bo; Li, Hong‐Tao; Li, De‐Zhu
Abstract: Chloroplast genome information helps improve the phylogenetic resolution and can act as organelle‐scale barcodes in recently radiated plant groups. Previously we reported that nine universal primer pairs could amplify angiosperm whole chloroplast genomes by long‐range polymerase chain reaction and using next‐generation sequencing. Although these primers show high universality and efficiency for sequencing whole chloroplast genomes in angiosperms, they did not fully resolve the following two issues surrounding sequencing angiosperm chloroplast genomes: (i) approximately 30% of angiosperms cannot be amplified successfully; and (ii) only fresh leaves can be applied. In this study, we designed another set of 15 universal primer pairs for amplifying angiosperm whole chloroplast genomes to complement the original nine primer pairs. Furthermore, we designed a primer pair for nuclear ribosomal DNAs (nrDNAs). To validate the functionality of the primers, we tested 44 species with silica gel‐dried leaves and 15 species with fresh leaves that have been shown to not be amplified with the original nine primer pairs. The result showed that, in 65.9% and 88.6% of the 44 species with silica gel‐dried leaves, the whole chloroplast genome and nrDNAs could be amplified, respectively. In addition, all 15 fresh leaf samples could have the whole chloroplast genome successfully amplified. The nrDNAs comprise partial sequences of 18S and 26S, along with the complete sequence of 5.8S and the internal transcribed spacers ITS1 and ITS2. The mean size of nrDNA was 5800 bp. This study shows that the 15 universal primer set is an indispensable tool for amplifying whole chloroplast genomes in angiosperms, and these are an important supplement to the nine reported primer pairs.